2014
DOI: 10.1371/journal.pone.0093290
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella Induces Stomatal Closure via NADPH Oxidase-Dependent ROS Production and Its Effects on Instantaneous Water Use Efficiency in Vicia faba

Abstract: Reactive oxygen species (ROS) have been established to participate in stomatal closure induced by live microbes and microbe-associated molecular patterns (MAMPs). Chlorella as a beneficial microorganism can be expected to trigger stomatal closure via ROS production. Here, we reported that Chlorella induced stomatal closure in a dose-and time-dependent manner in epidermal peels of Vicia faba. Using pharmacological methods in this work, we found that the Chlorella-induced stomatal closure was almost completely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 75 publications
(104 reference statements)
4
27
0
Order By: Relevance
“…Recently, stomatal aperture is also observed to change in response to numerous biotic cues (Sawinski et al 2013). For instance, stomata can actively close on detection of the presence of live bacteria, barley mildew, yeast, yeast elicitor (YEL), Chlorella and purified microbe-associated molecular patterns (MAMPs) by activating a series of complex signaling transduction pathways (Melotto et al 2006;Khokon et al 2010a;Koers et al 2011;Gao et al 2013;Li et al 2014b). Interestingly, Kumar et al (2012) found that the root inoculation of the Bacillus subtilis FB17 could also induce stomatal closure to prevent foliar pathogen entry into leaf inner tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, stomatal aperture is also observed to change in response to numerous biotic cues (Sawinski et al 2013). For instance, stomata can actively close on detection of the presence of live bacteria, barley mildew, yeast, yeast elicitor (YEL), Chlorella and purified microbe-associated molecular patterns (MAMPs) by activating a series of complex signaling transduction pathways (Melotto et al 2006;Khokon et al 2010a;Koers et al 2011;Gao et al 2013;Li et al 2014b). Interestingly, Kumar et al (2012) found that the root inoculation of the Bacillus subtilis FB17 could also induce stomatal closure to prevent foliar pathogen entry into leaf inner tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Our present work showed that optimal concentrations of Chlorella suspension caused significant reductions in leaf stomatal aperture, stomatal conductance (g s ) and transpiration rate (E) without a parallel reduction in net photosynthetic rate (P n ) and intercellular CO 2 concentration (C i ), favoring a higher WUE i in Vicia faba. 12 The chlorophyll fluorescence and content analysis further demonstrated that Chlorella did not affect plant photosynthetic reactions center after short-term foliar application. 12 Nevertheless, whether the leaf chlorophyll fluorescence and content are influenced after treatment with appropriate concentrations of Chlorella suspension for a longer time needs to be further assessed.…”
mentioning
confidence: 94%
“…12 The chlorophyll fluorescence and content analysis further demonstrated that Chlorella did not affect plant photosynthetic reactions center after short-term foliar application. 12 Nevertheless, whether the leaf chlorophyll fluorescence and content are influenced after treatment with appropriate concentrations of Chlorella suspension for a longer time needs to be further assessed. Taken together, these results preliminarily suggest that optimal concentrations of Chlorella suspension can improve the WUE i in plants after short-term foliar spray, mainly attributing to a reduction in stomatal conductance above the threshold, under which transpiration rates are diminished significantly while photosynthetic rates hardly affected.…”
mentioning
confidence: 94%
See 2 more Smart Citations